2012
DOI: 10.1002/jor.22133
|View full text |Cite
|
Sign up to set email alerts
|

Ferric ion could facilitate osteoclast differentiation and bone resorption through the production of reactive oxygen species

Abstract: Iron overload is widely regarded as a risk factor for osteoporosis. It has been demonstrated that iron can inhibit osteoblast differentiation. However, the effects of iron on osteoclast differentiation and bone resorption remain controversial. In this study, we found that ferric ion promoted Receptor Activator of Nuclear Factor k B Ligand (RANKL)-induced osteoclast (OC) formation in both RAW264.7 cells and bone marrow-derived macrophages (BMMs), and this effect was accompanied by elevated levels of reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 42 publications
7
72
3
Order By: Relevance
“…In other words, excess iron promoted the activity of osteoclasts, and then elevated bone resorption process, with resultant loss of bone strength. In terms of the molecular mechanisms, previous studies have demonstrated that intracellular iron retention would cause massive production of reactive oxygen species (ROS) through Fenton reaction (Fridovich, 1978;Galaris and Pantopoulos, 2008;Halliwell and Gutteridge, 1990), and ROS is postulated to be an instigator of bone resorption (Jia et al, 2012). Jia and colleagues demonstrated that iron overload could promote osteoclast differentiation and bone resorption through stimulation of ROS (Ishii et al, 2009;Yamasaki and Hagiwara, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, excess iron promoted the activity of osteoclasts, and then elevated bone resorption process, with resultant loss of bone strength. In terms of the molecular mechanisms, previous studies have demonstrated that intracellular iron retention would cause massive production of reactive oxygen species (ROS) through Fenton reaction (Fridovich, 1978;Galaris and Pantopoulos, 2008;Halliwell and Gutteridge, 1990), and ROS is postulated to be an instigator of bone resorption (Jia et al, 2012). Jia and colleagues demonstrated that iron overload could promote osteoclast differentiation and bone resorption through stimulation of ROS (Ishii et al, 2009;Yamasaki and Hagiwara, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In osteoclasts, iron excess stimulates osteoclastogenesis by supporting mitochondrial respiration, [18][19][20] while sequestering iron from osteoclasts inhibits their maturation and function. [21][22] In contrast, osteoblast function is suppressed by iron excess in osteoblast cell lines, [23][24][25] while iron chelation using deferoxamine (DFO) seems to exert positive effects on osteoblast maturation.…”
Section: Introductionmentioning
confidence: 99%
“…67 Moreover, ferric ionic state successfully promoted Schwann cell and osteoclast differentiation. 68,69 These phenomena may help explain why transferrin and ferric ions play indispensable roles in driving motor neuron differentiation.…”
Section: Discussionmentioning
confidence: 99%